The Effect of Policy Implementation of Law Number 33 of 2004 concerning Central and Regional Financial Balance on the Performance of the Regional Government of Banten Province - Andi Ahmad Dara (GoAcademica Research & Publishing, 2021)
The purpose of this study is to analyze and find out how much influence the implementation of the central and regional financial balance policies, either partially or simultaneously, has on the performance of local government development in Banten Province. The population in this study were employees of the Banten Province Government Work Unit from echelon I to echelon IV as many as 888 employees with 90 samples taken by purposive sampling method. Data testing is done by using path analysis. The results show that the X to Y structure is the influence of the policy implementation variable (X) on the performance variable of the Banten Provincial Government (Y) with Path Analysis of 67.9%, and the influence value outside the model is 32.1%, where the value of the multiple correlation coefficient R = 0.824, it can be stated that the degree of influence is very close compared to other variables not examined, and in the sub-structures X1, X2, X3, and X4 to Y, the influence of aspects of policy implementation are aspects of policy content (X1), information (X2), support (X3) and the distribution of potential (X4) on Government performance of Banten Province (Y) with Path Analysis of 67.9% and the influence value outside the model is 32.1% where the multiple correlation coefficient value R = 0.824 can be stated the degree of influence is very close compared to the other variables. Others not investigated.